A Co-MOF-derived Co9S8@NS-C electrocatalyst for efficient hydrogen evolution reaction. Issue 11 (3rd February 2021) - Li, Yun-Wu; Wu, Qian; Ma, Rui-Cong; Sun, Xiao-Qi; Li, Dan-Dan; Du, Hong-Mei; Ma, Hui-Yan; Li, Da-Cheng; Wang, Su-Na; Dou, Jian-Min
Abstract : A porous Co9 S8 @NS-C-900 composite was fabricated by the pyrolysis of crystal Co-MOF involving thiourea. The composite exhibits efficient electrocatalytic activities and long-term durabilities towards HER in alkaline electrolytes. Abstract : The exploitation of efficient hydrogen evolution reaction (HER) electrocatalysts has become increasingly urgent and imperative; however, it is also challenging for high-performance sustainable clean energy applications. Herein, novel Co9 S8 nanoparticles embedded in a porous N, S-dual doped carbon composite (abbr. Co9 S8 @NS-C-900) were fabricated by the pyrolysis of a single crystal Co-MOF assisted with thiourea. Due to the synergistic benefit of combining Co9 S8 nanoparticles with N, S-dual doped carbon, the composite showed efficient HER electrocatalytic activities and long-term durability in an alkaline solution. It shows a small overpotential of −86.4 mV at a current density of 10.0 mA cm −2, a small Tafel slope of 81.1 mV dec −1, and a large exchange current density ( J 0 ) of 0.40 mA cm −2, which are comparable to those of Pt/C. More importantly, due to the protection of Co9 S8 nanoparticles by the N, S-dual doped carbon shell, the Co9 S8 @NS-C-900 catalyst displays excellent long-term durability. There is almost no decay in HER activities after 1000 potential cycles or it retains 99.5% of the initial current after 48 h.